A turn-on fluorescent probe based on indolizine for the detection of sulfite. (8th April 2022) - Cui, Renle; Gao, Yunlong; Ge, Haiyan; Shi, Guowei; Li, Yongchao; Liu, Hao; Ma, Chuanjun; Ge, Yanqing; Liu, Caihong
Abstract : Numerous SO3 2− /HSO3 − fluorescent probes have been reported based on various mechanisms. Abstract : Numerous SO3 2− /HSO3 − fluorescent probes have been reported based on various mechanisms. However, most probes are constructed from classic dyes such as coumarin, BODIPY, and cyanine. The development of a new fluorophore with excellent performance is still required. CRL-1, a turn-on fluorescent probe based on indolizines, was developed for the detection of sulfite. Compared with other analytes, probe CRL-1 showed a short response time (within 10 s) and excellent selectivity and had strong fluorescence emission at 458 nm. The probe's LOD was 8.1 μM. Furthermore, cell imaging experiments suggested that the probe can be useful in biological systems.